Pediatric dermatology I infections and infestations - Cohen, Bernard, 1951-; Swinyer, Leonard J., 1940-; Marion & Roberta Sulzberger Institute for Dermatologic Communication and Education; American Academy of Dermatology. Committee on Audiovisual Education ([Evanston, Ill.] : American Academy of Dermatology, Committee on Audiovisual Education, 1988)
(Producer) A presentation of infections encountered in children, including bacterial, viral, and fungal infections -- plus infestations and arthropod bites
'From the collections of Bernard Cohen ... and Leonard J. Swinyer.'
Keywords: Dermatomycoses -- child; Dermatomycoses -- infant; Skin Diseases, Infectious -- child; Skin Diseases, Infectious -- infant; Skin Diseases, Parasitic -- child; Skin Diseases, Parasitic -- infant